2020
DOI: 10.1016/j.jamcollsurg.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of Overtreatment of Rectal Cancer by Selective Chemoradiotherapy: Results of the Optimized Surgery and MRI-Based Multimodal Therapy Trial

Abstract: BACKGROUND: Neoadjuvant chemoradiotherapy (nCRT) in patients with rectal cancer carries a high risk of adverse effects. The aim of this study was to examine the selective application of nCRT based on patient risk profile, as determined by MRI, to find the optimal range between undertreatment and overtreatment. STUDY DESIGN: In this prospective multicenter observational study, nCRT before total mesorectal excision (TME) was indicated in high-risk patients with involved or threatened mesorectal fascia ( 1 mm), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…2020. 3 Summary: A standard treatment for locoregionally advanced rectal cancer involves neoadjuvant radiation and chemotherapy followed by surgery. Although nLCRT has been shown to decrease the risk of LR, some patients experience treatment-related side effects and may not benefit from it.…”
Section: Rullier Et Al Organ Preservation With Chemoradiotherapy Plus Local Excision For Rectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…2020. 3 Summary: A standard treatment for locoregionally advanced rectal cancer involves neoadjuvant radiation and chemotherapy followed by surgery. Although nLCRT has been shown to decrease the risk of LR, some patients experience treatment-related side effects and may not benefit from it.…”
Section: Rullier Et Al Organ Preservation With Chemoradiotherapy Plus Local Excision For Rectal Cancermentioning
confidence: 99%
“…Although nLCRT has been shown to decrease the risk of LR, some patients experience treatment-related side effects and may not benefit from it. The aim of this prospective multicenter observational study 3 was to evaluate the selective omission of nLCRT, based on risk as determined by MRI. The study included patients with cT2-4, any cN, cM0 histologically confirmed rectal adenocarcinoma who were candidates for TME.…”
Section: Rullier Et Al Organ Preservation With Chemoradiotherapy Plus Local Excision For Rectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Neoadjuvant chemoradiotherapy followed by radical resection is the standard treatment for stage III RC patients and stage II RC patients with high-risk factors 1 , 2 . While lymph node metastasis, vessel invasion, R1 or R2 resection, and high tumor stage are identified as unfavorable prognostic factors, patients with comparable risk elements have a wide variation of oncology outcomes 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Dennoch wurden in der Gruppe der primär operierten Patienten 18 % der Karzinome pathologisch lediglich als T1-2N0 diagnostiziert [3]. In der OCUM-Studie wuchs trotz protokollgeführter MRT-Diagnostik dieser Anteil auf 27,3 % an [4].…”
unclassified